Combined Ultraviolet-C and Pasteurization Methods to Extend the Shelf Life of Cow's Milk - Rengga, Wara Dyah Pita; Ridwan Dani Hibatullah; Miftakhul Izza Arinanda; Muhammad Fajrul Rohman; Ria Wulansarie; Rusiyanto (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2024)
Milk is classified as an animal food that is easily damaged because it contains high nutrients and water, so it is ideal for microbial growth. The common milk preservation technique is pasteurization. However, in pasteurization, heat-resistant bacteria are still able to survive. This study aims to find Total Plate Counternative methods of processing cow's milk, namely by innovating the combination of ultraviolet-C radiation and pasteurization methods to reduce the number of milk microbes while still prioritizing quality and safety. The ultraviolet -C modified pasteurization apparatus was given three treatments, i.e. radiation process then pasteurization process, pasteurization process then radiation process, and simultaneous (combined) process. The results showed that the simultaneous process resulted in a reduction percentage of bacteria of 99.996%, from the number of bacteria in milk which was originally 6.2×106 to 1×103 CFU/mL. The shelf life of milk with the simultaneous method showed the best results with an TOTAL PLATE COUNT test of 10 CFU/ml after 6 months of storage. The results showed that the degree of acidity (pH) before and after treatment of the three sterilization methods did not show a significant change. Simultaneous method or ultraviolet C radiation modified pasteurization process can be an Total Plate Counternative method in milk sterilization and increase shelf life.